2005
DOI: 10.1002/cbdv.200490163
|View full text |Cite
|
Sign up to set email alerts
|

A New Destruxin as Inhibitor of Vacuolar-Type H+-ATPase ofSaccharomyces cerevisiae

Abstract: In the course of our screening efforts to discover small molecules as selective inhibitors of vacuolar-type H+-ATPase of Saccharomyces cerevisiae, we have identified eight active destruxins, 1-8, from the fungus Metarhizium anisopliae. The structures were elucidated by extensive 1D- and 2D-NMR spectroscopy, and MS spectrometry. One of these compounds, 8, a regioisomer of chlorohydrin destruxin E (7), is a new destruxin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…1) used in this study were isolated and identified as described in the literature. [9][10][11] Some important properties of these compounds have also been reviewed and can be found elsewhere.…”
Section: Introductionmentioning
confidence: 99%
“…1) used in this study were isolated and identified as described in the literature. [9][10][11] Some important properties of these compounds have also been reviewed and can be found elsewhere.…”
Section: Introductionmentioning
confidence: 99%
“…Destruxins, especially DB, are inhibitors of V‐ATPase (Vazquez et al ., ; Bandani et al ., ). V‐ATPase maintains an acidic environment within lysosomes and vacuoles to help digest ingested materials.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, different insect and human cells have been damaged by destruxins, and several reports have indicated that destruxins changed intracellular calcium ion balances (Dumas et al ., ; Dumas et al ., ; Dumas et al ., ). In addition, destruxins were a kind of calcium ionophore (Vazquez et al ., ) and inhibitors of vacuolar H + adenosine triphosphatase (V‐H + ‐ATPase) (Muroi et al ., ; Bandani et al ., ). However, the molecular mechanisms of destruxins have yet to be illustrated.…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been found that 1 has several unique biological activities,7 including antiproliferative activity against P388 leukemic cells,8 the inhibition of the accumulation of lipid droplets in J774 macrophages,9 and the ability to decrease the amount of amyloid‐β (Aβ) generated without affecting the β‐amyloid‐cleaving enzyme (BACE) or presenilin (PS)/γ‐secretase activity 10. In particular, compound 1 is a more potent V‐ATPase inhibitor than any other member of the destruxin family11 and could therefore be a promising candidate drug for use in cancer therapies because V‐ATPase plays an important role in allowing cancer cells to behave invasively 12. Intriguingly, it has recently been reported that 1 induces morphological changes in osteoclast‐like multinuclear cells (OCLs) reversibly at a lower concentration than that required to affect V‐ATPase activity in the OCLs, resulting in inhibition of bone resorption without causing cell death 13.…”
Section: Introductionmentioning
confidence: 99%